Antibacterial Activity of Zerumbone from Extract of Zingiber zerumbet (L.) Roscoe ex Smith Rhizomes - Soerya Dewi Marliyana; Desi Suci Handayani; Nida Nafisah Hayati; Risna Ramadhani (Universitas Sebelas Maret, 2025)
The rhizome of Zingiber zerumbet, known as Lempuyang Gajah, is commonly used in the community for medicinal purposes due to its diverse biological activities, particularly its antibacterial compounds. Among these compounds, zerumbone is one of the major secondary metabolites found in Z. zerumbet rhizomes. This research focused on the isolation of zerumbone and the exploration of its antibacterial properties. The isolation process involved the use of the maceration method with acetone as the solvent, while various chromatographic techniques such as Liquid Vacuum Chromatography, Column Chromatography, and Thin Layer Chromatography were employed for fractionation and purification of zerumbone. The identification of zerumbone was accomplished through GC-MS data analysis. The antibacterial activity of zerumbone was tested against Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, and Pseudomonas aeruginosa using the agar diffusion method. This compound exhibited moderate antibacterial activity against P. aeruginosa with an inhibition zone of 9.42 mm. The rhizome of Z. zerumbet can serve as an alternative source of zerumbone for further studies in the field of medicine.